No-till with high biomass cover crops and invasive legume mulches increased total soil carbon after three years of collard production. Issue 1 (2nd January 2017) - Mulvaney, M. J.; Wood, C. W.; Balkcom, K. S.; Kemble, J.; Shannon, D. A.
ABSTRACT: Studies have shown that conversion to conservation tillage from conventional tillage does not increase total soil organic carbon (SOC) significantly in the short term (<5 yrs). While no-till increases total SOC in the medium to long term, it was hypothesized that the inclusion of high biomass cover crops and organic mulches may increase total SOC in the short term. The use of invasive, perennial leguminous species as mulch may sustainably increase SOC during limited-input fall vegetable production. The objective of this study, conducted in Alabama (USA), was to quantify total SOC changes due to organic mulches and forage soybean ( Glycine max (L.) Merr. cv. Derry) as a summer cover crop after conversion to no-till during limited-input fall collard ( Brassica oleracea L.) production. Forage soybean as a summer cover crop did not increase SOC. No-till without mulch (control treatment) significantly increased SOC at 0–5 cm from 6.3 to 14.0 g kg −1 soil in 3 yrs, whereas inclusion of cut-and-carry mulches increased SOC to ≥22.6 g kg −1 soil. Treatments did not affect collard yield, which averaged 17, 863 kg ha −1 yr −1 . This represents a novel, limited-input system that may help control on-farm invasive species while sustainably increasing SOC in the short term.